2019
DOI: 10.1002/cphc.201900902
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Effects on the Electrocatalytic Performance of Iridium‐Based Nanoparticles for Oxygen Evolution in Rotating Disc Electrodes

Abstract: Proton exchange membrane water electrolysers are very promising renewable energy conversion devices that produce hydrogen from sustainable feedstocks. These devices are mainly limited by the sluggish kinetics of the oxygen evolution reaction (OER). Ir‐based nanoparticles are both reasonably active and stable for the OER in acidic media. The electrolyte composition and the pH may play a crucial role in electrocatalysis, yet they have been widely overlooked for the OER. Herein, we present a study on the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 81 publications
5
39
0
Order By: Relevance
“…Chronopotentiometric studies have to be analysed carefully as they can give misleading interpretation of the catalytic performance of different materials. We recently showed that the initial overpotential in chronopotentiometric studies determines the apparent stability of Ir NPs as the rate of degradation is much faster at higher overpotentials . In this work, the initial overpotentials of the different Ir NPs are similar (Figure a).…”
Section: Figuresupporting
confidence: 58%
See 1 more Smart Citation
“…Chronopotentiometric studies have to be analysed carefully as they can give misleading interpretation of the catalytic performance of different materials. We recently showed that the initial overpotential in chronopotentiometric studies determines the apparent stability of Ir NPs as the rate of degradation is much faster at higher overpotentials . In this work, the initial overpotentials of the different Ir NPs are similar (Figure a).…”
Section: Figuresupporting
confidence: 58%
“…To ensure a sustainable use of this precious metal, a careful design of the catalyst is needed . Much effort has been recently devoted to develop Ir‐based nanoparticulate catalysts to maximise the electrochemical activity per amount of Ir …”
Section: Figurementioning
confidence: 99%
“…There is no agreement on an OER activation protocol, but in general, two different methods can be used. Sometimes, the electrode is cycled under OER potential range until a stable CV is reached [30,53], but most frequently fast cycling between a low potential (like 0.05 V or 0.025 V versus RHE) and a potential close to the onset of OER (between 1.3 V and 1.45 V versus RHE) is employed until stable CVs are reached [20,29,36,38,39]. In the present study, two different potential windows were compared.…”
Section: Resultsmentioning
confidence: 99%
“…The second activation consisted of cycling between 0.05 and 1.45 V versus RHE. This second protocol is similar or closer to the potential range usually chosen in the literature [20,29,36,38,39]. The OER activity was recorded by performing a minimum of eight cycles between 1.2 and 1.6 V versus RHE, 1600 rpm, 20 mV s −1 , under Ar atmosphere in a 0.1 M HClO 4 (Merck, Suprapur, 70%) electrolyte.…”
Section: Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation